2017
DOI: 10.1021/acsami.7b10666
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar Resistive Switching in Ag@TiO2 Core–Shell Nanowires

Abstract: Nonpolar resistive switching (RS), a combination of bipolar and unipolar RS, is demonstrated for the first time in a single nanowire (NW) system. Exploiting Ag@TiO core-shell (CS) NWs synthesized by postgrowth shell formation, the switching mode is controlled by adjusting the current compliance effectively, tailoring the electrical polarity response. We demonstrate ON/OFF ratios of 10 and 10 for bipolar and unipolar modes, respectively. In the bipolar regime, retention times could be controlled up to 10 s, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Initially, a positive bias voltage of about 7 V was necessary to electrically connect the two electrodes by the formation of Cu filaments in the SiO 2 shell (electroforming process). [231] Exploiting the formation/rupture of metallic filaments across the shell layer, resistive switching was observed also in Ag-TiO 2 coreshell NWs by Manning et al [232] In this case, a nonpolar resistive switching was observed as a consequence of the formation/ rupture of Ag filaments through the TiO 2 shell layer that enabled to connect the Ag electrodes to the Ag core of the NW. The device was turned in the LRS (write) by applying a positive voltage to the Cu electrode, giving rise to the bipolar resistive switching behavior reported in Figure 13a.…”
Section: Wwwadvelectronicmatdementioning
confidence: 87%
See 1 more Smart Citation
“…Initially, a positive bias voltage of about 7 V was necessary to electrically connect the two electrodes by the formation of Cu filaments in the SiO 2 shell (electroforming process). [231] Exploiting the formation/rupture of metallic filaments across the shell layer, resistive switching was observed also in Ag-TiO 2 coreshell NWs by Manning et al [232] In this case, a nonpolar resistive switching was observed as a consequence of the formation/ rupture of Ag filaments through the TiO 2 shell layer that enabled to connect the Ag electrodes to the Ag core of the NW. The device was turned in the LRS (write) by applying a positive voltage to the Cu electrode, giving rise to the bipolar resistive switching behavior reported in Figure 13a.…”
Section: Wwwadvelectronicmatdementioning
confidence: 87%
“…Cu–core SiO 2 shell NWs dispersed in ethylcellulose have been proposed as building blocks for the realization of fully printed memristors . Exploiting the formation/rupture of metallic filaments across the shell layer, resistive switching was observed also in Ag–TiO 2 core–shell NWs by Manning et al In this case, a nonpolar resistive switching was observed as a consequence of the formation/rupture of Ag filaments through the TiO 2 shell layer that enabled to connect the Ag electrodes to the Ag core of the NW. The switching mechanism was favored by the highly defective polycrystalline microstructure of TiO 2 and by the Ag inclusions in the shell layer due to the growth process.…”
Section: Resistive Switching In Single Isolated Nanowiresmentioning
confidence: 99%
“…R jxn is a consequence of an electrically insulating few nm thick polyvinolpyrollidone (PVP) layer that forms a metal-insulator-metal configuration where ever NWs overlap to form a junction 23 . Modification of the PVP surface layer can give resistive switching memory effects 24,25 , or enhance the thermal and chemical stability of the Ag NWNs 17,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Ag@PVP plates). During the breakdown of a MIM junction, the growth of a conducting filament (CF) bridging the metal plates takes place and this can be regulated by distinct mechanisms [16,[19][20][21] including thermochemical, electrochemical metallization, and valence change. With the filament gradual growth, a drastic reduction in the characteristic resistance of the junction can be measured.…”
Section: Introductionmentioning
confidence: 99%